2012
DOI: 10.1007/s00221-012-3008-9
|View full text |Cite
|
Sign up to set email alerts
|

Corticomotor control of deep abdominal muscles in chronic low back pain and anticipatory postural adjustments

Abstract: Contralateral transversus abdominis muscle (cTrA) is known to be anticipatory to rapid focal movement. The activation of ipsilateral TrA (iTrA) follows cTrA, but their anticipatory interaction in healthy subjects seems to be delayed in low back pain (LBP) patients. TrA delay in LBP is linked with reorganization of the primary motor cortex (M1), thus supporting that cortical changes underlie the altered postural control. Our study tested whether differences in postural adjustments were present in LBP for TrA on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
80
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 56 publications
3
80
0
6
Order By: Relevance
“…Studies using transcranial magnetic stimulation to examine corticomotor excitability in chronic pain have shown altered responses in a number of chronic pain populations. The findings have generally indicated an increase in corticomotor excitability 115,116 and a reduction in intracortical inhibition [117][118][119][120][121][122][123] in the affected body region. These findings appear to be supported by a functional MRI (fMRI)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using transcranial magnetic stimulation to examine corticomotor excitability in chronic pain have shown altered responses in a number of chronic pain populations. The findings have generally indicated an increase in corticomotor excitability 115,116 and a reduction in intracortical inhibition [117][118][119][120][121][122][123] in the affected body region. These findings appear to be supported by a functional MRI (fMRI)…”
mentioning
confidence: 99%
“…124 However, some authors have reported normal 121 or reduced corticomotor excitability 122 in chronic pain populations, and it is likely that the outcomes are influenced by the pain condition or methodological differences among studies.…”
mentioning
confidence: 99%
“…Poor function of trunk deep muscles is associated with LBP (Abdelraouf and Abdel-aziem, 2016). Moreover, activation of deep abdominal muscles such as TrA and IO is delayed and co-activation is absent in patients with low back pain (Massé-Alarie et al, 2012).…”
mentioning
confidence: 99%
“…El feedforward se define como las acciones anticipatorias/preventivas que ocurren antes de la detección sensorial de una disrupción de la homeostasis con base en experiencias anteriores 15 . Los ajustes de anticipación postural subyacen a la capacidad del sistema nervioso de contrarrestar las fuerzas de reacción inducidas por un movimiento focal antes de efectuar el propio movimiento 16 . En este contexto, el músculo transverso abdominal (TrA) es uno de los componentes de la musculatura profunda abdominal que están involucrados en el control del tronco 17 , contribuyendo en los ajustes posturales anticipatorios del control segmentario de la columna lumbosacra durante movimientos focales 18 .…”
unclassified
“…Se podría concluir que el TrA y el oblicuo interno parecen contribuir a controlar la zona lumbar de manera bilateral durante los movimientos. Sin embargo, en pacientes con dolor lumbar crónico, se detectan cambios significativos en los patrones de ajuste postural anticipatorio tanto en el TrA como en el oblicuo interno que pueden ser el resultado de una disfunción de los mecanismos que subyacen la corteza motora primaria en su vinculación con el control de la estabilidad de la columna 16 . La musculatura respiratoria también es reclutada por el SNC para satisfacer las demandas de estabilidad.…”
unclassified